2022
DOI: 10.3390/plants12010063
|View full text |Cite
|
Sign up to set email alerts
|

Rebalancing Nutrients, Reinforcing Antioxidant and Osmoregulatory Capacity, and Improving Yield Quality in Drought-Stressed Phaseolus vulgaris by Foliar Application of a Bee-Honey Solution

Abstract: Bee-honey solution (BHS) is considered a plant growth multi-biostimulator because it is rich in osmoprotectants, antioxidants, vitamins, and mineral nutrients that can promote drought stress (DtS) resistance in common bean plants. As a novel strategy, BHS has been used in a few studies, which shows that the application of BHS can overcome the stress effects on plant productivity and can contribute significantly to bridging the gap between agricultural production and the steady increase in population under clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…A result of this was limited nutrient uptake because transpiration was reduced, ions were immobilized, membrane permeability was reduced, and the roots were not able to absorb nutrients [93]. It has been reported that N, P, and K uptake decreases with an increased duration of water deficit [94]. Insufficient soil moisture and osmotic stress are two factors that contribute to decreased nutrient uptake.…”
Section: Discussionmentioning
confidence: 99%
“…A result of this was limited nutrient uptake because transpiration was reduced, ions were immobilized, membrane permeability was reduced, and the roots were not able to absorb nutrients [93]. It has been reported that N, P, and K uptake decreases with an increased duration of water deficit [94]. Insufficient soil moisture and osmotic stress are two factors that contribute to decreased nutrient uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Encoring growth, yield, and pod quality of excessive N-stressed P. vulgaris plants by foliar spraying with DHS indicated that this multi-bio-stimulator (mBS; DHS) has multiple mechanisms (e.g., osmoprotectants, different antioxidants, including ascorbate and B-group vitamins, and various nutrients, including iodine and selenium). All of these BSs support plants to encore their development and growth because of the mitigation of excessive N stress [16,17,24].…”
Section: Discussionmentioning
confidence: 99%
“…), antioxidant compounds (ascorbate, AsA; glutathione, GSH; proline; alkaloids; flavonoids; carotenoids; α-tocopherol; phenolics; etc.) [12,13], and osmoregulatory compounds (ORCs) like simple sugars, soluble proteins, and glycine betaine [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The SBH was prepared [12,15,26] by adding 10 mL to each L distilled water and enriched with 200 μg Sim per L of solution. The SBH (1.0% beehoney solution enriched with 200 μg silymarin per L of solution) was nominated for this principal study because it conferred the best findings among many treatments (0.5% bee-honey solution, 1.0% bee-honey solution, 1.5% bee-honey solution, 1.0% bee-honey solution enriched with 100 μg silymarin per L of solution, 1.0% bee-honey solution enriched with 200 μg silymarin per L of solution, and 1.0% bee-honey solution enriched with 300 μg silymarin per L of solution) applied in a preliminary study (data not shown).…”
Section: Experimental Setup and Treatmentsmentioning
confidence: 99%